Differential Localization of Mre Proteins with PBP2 in Rhodobacter sphaeroides - Slovak, Peter M. (American Society for Microbiology, 2006)
In Rhodobacter sphaeroides, MreB, MreC, MreD, PBP2, and RodA are encoded at the same locus. The localizations of PBP2, MreB, and MreC, which have all been implicated in the synthesis of the peptidoglycan layer, were investigated under different growth conditions to gain insight into the relationships between these proteins. Immunofluorescence microscopy showed that PBP2 localized to specific sites at the midcell of elongating cells under both aerobic and photoheterotrophic conditions. Visualizing PBP2 at different stages of the cell cycle showed that in elongating cells, PBP2 was found predominately at the midcell, with asymmetric foci and bands across the cell. PBP2 remained at midcell until the start of septation, after which it moved to midcell of the daughter cells. Deconvolution and three-dimensional reconstructions suggested that PBP2 forms a partial ring at the midcell of newly divided cells and elongated cells, while in septating cells, partial PBP2 rings were present at one-quarter and three-quarter positions. Due to the diffraction limits of light microscopy, these partial rings could represent unresolved helices. Colocalization studies showed that MreC always colocalized with PBP2, while MreB colocalized with PBP2 only during elongation; during septation, MreB remained at the septation site, whereas PBP2 relocalized to the one-quarter and three-quarter positions. These results suggest that PBP2 and MreC are involved in peptidoglycan synthesis during elongation and that this occurs at specific sites close to midcell in R. sphaeroides.